2011
DOI: 10.1038/nmat2976
|View full text |Cite
|
Sign up to set email alerts
|

Support nanostructure boosts oxygen transfer to catalytically active platinum nanoparticles

Abstract: Interactions of metal particles with oxide supports can radically enhance the performance of supported catalysts. At the microscopic level, the details of such metal-oxide interactions usually remain obscure. This study identifies two types of oxidative metal-oxide interaction on well-defined models of technologically important Pt-ceria catalysts: (1) electron transfer from the Pt nanoparticle to the support, and (2) oxygen transfer from ceria to Pt. The electron transfer is favourable on ceria supports, irres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
768
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(818 citation statements)
references
References 49 publications
42
768
1
7
Order By: Relevance
“…As shown in Figure S3 (Supporting Information), no structure reconstruction is found to occur in all of the cases under the temperature of 353 K. Even the temperature increases to 500 K, which far exceeds the typical experimental reaction temperature, the structures of the TM‐V 2 CO 2 still remain in good shape, indicative of the high stability of TM‐V 2 CO 2 . Moreover, the interaction between the promoter atoms and surface O atoms follows the type of electron transfer, due to the relatively large electron transfer (larger than 0.7 e) from TM atoms to V 2 CO 2 and the high formation energy of an oxygen vacancy (larger than 3.0 eV) on both the pure and TM‐promoted V 2 CO 2 surface, which is similar to that of Pt–CeO 2 catalyst 27. On the surface of TM‐promoted V 2 CO 2 , H prefers to adsorb on the top of the O atom which is not bonded with the TMs, as shown in Figure 2 a–c.…”
Section: Resultsmentioning
confidence: 61%
“…As shown in Figure S3 (Supporting Information), no structure reconstruction is found to occur in all of the cases under the temperature of 353 K. Even the temperature increases to 500 K, which far exceeds the typical experimental reaction temperature, the structures of the TM‐V 2 CO 2 still remain in good shape, indicative of the high stability of TM‐V 2 CO 2 . Moreover, the interaction between the promoter atoms and surface O atoms follows the type of electron transfer, due to the relatively large electron transfer (larger than 0.7 e) from TM atoms to V 2 CO 2 and the high formation energy of an oxygen vacancy (larger than 3.0 eV) on both the pure and TM‐promoted V 2 CO 2 surface, which is similar to that of Pt–CeO 2 catalyst 27. On the surface of TM‐promoted V 2 CO 2 , H prefers to adsorb on the top of the O atom which is not bonded with the TMs, as shown in Figure 2 a–c.…”
Section: Resultsmentioning
confidence: 61%
“…Earlier, oxygen migration was supported by TPD and Auger spectroscopy for the Rh-ceria system, 83,84 and recently an STM study gave further evidence. 85 Moreover, Vayssilov et al 13 showed the coexistence of two different interaction mechanisms, a purely electronic effect involving electron transfer from Pt to CeO 2 and a second channel, involving transport of activated oxygen from nanostructured ceria to Pt, i.e. oxygen spillover.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…This is due to the peculiar redox properties and oxygen storage capacity of ceria, as well as to synergetic effects between the ceria support and metals. [8][9][10][11][12][13] Noble metals, especially Rh, have proven to be excellent catalysts for dehydrogenation reactions, [14][15][16] but their prices are prohibitively high. As an alternative, the less expensive transition metal Co is a promising catalyst for the steam reforming of ethanol (SRE).…”
Section: Introductionmentioning
confidence: 99%
“…These findings based on results obtained for the oxidation of single crystal surfaces, however, can-not simply be assigned to the equivalent nanoparticle facets: the presence of vicinal surfaces and edges, the higher defect density and the influence of the substrate which are present in nanoparticle systems may lead to a different oxidation behavior which in turn might also affect catalyst performance 13,52,53 . This underlines the explicit need for experimental in-situ studies of oxygeninduced nanoparticle shape changes and bulk oxide formation under realistic conditions.…”
Section: Introductionmentioning
confidence: 96%